2018
DOI: 10.1051/0004-6361/201833936
|View full text |Cite
|
Sign up to set email alerts
|

From solar to stellar brightness variations

Abstract: Context. Comparison studies of Sun-like stars with the Sun suggest an anomalously low photometric variability of the Sun compared to Sun-like stars with similar magnetic activity. Comprehensive understanding of stellar variability is needed, to find a physical reasoning for this observation. Aims. We investigate the effect of metallicity and effective temperature on the photometric brightness change of Sun-like stars seen at different inclinations. The considered range of fundamental stellar parameters is suff… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 50 publications
1
48
0
Order By: Relevance
“…It was shown earlier that metallicity has a significant effect on facular contrasts, and thus on stellar variability in solar-like stars (Karoff et al 2018;Witzke et al 2018). In this work, our aim is to understand the effect of metallicity on the detectability of the rotation periods in solar-like stars.…”
Section: Introductionmentioning
confidence: 94%
“…It was shown earlier that metallicity has a significant effect on facular contrasts, and thus on stellar variability in solar-like stars (Karoff et al 2018;Witzke et al 2018). In this work, our aim is to understand the effect of metallicity on the detectability of the rotation periods in solar-like stars.…”
Section: Introductionmentioning
confidence: 94%
“…At the same time, metallicity can affect other aspects of magnetic activity that we have not taken into account. For example, Witzke et al (2018) showed that, for a fixed activity level, metallicity affects the brightness contrasts between faculae and the photosphere, leading to differences in the optical variability and detectability of rotation. Karoff et al (2018) studied a solar analog with the same age but twice the metallicity of the Sun ([Fe/H]=+0.3).…”
Section: Implications For Activity-age Relationshipmentioning
confidence: 99%
“…The total photometric amplitude of 0.37 mmag for the solar cycle has been computed by Shapiro et al (2016). Such a small value was explained in Witzke et al (2018) by the incident combination of solar fundamental parameters and the spectral location of the Strömgren b and y pass bands. Furthermore, from Table B.1, it can be seen that 8 of the 27 stars with measured cycle periods exhibit a chromospheric activity cycle classified as excellent (flag chrom = 3).…”
Section: Activity Cycle Phase Differencementioning
confidence: 99%